2021
DOI: 10.1007/s11605-019-04492-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Nutritional Index and Systemic Immune-Inflammation Index Predict the Prognosis of Patients with HCC

Abstract: Introduction Systemic nutrition and inflammation are the critical factors in cancer initiation, evolution, and progression. This study aimed to evaluate the prognostic value of the prognostic nutritional index (PNI) and systemic immune-inflammation index (SII) in hepatocellular carcinoma (HCC) patients who underwent liver resection. Methods A total of 202 HCC patients met the criteria and were included in the study. The receiver operating characteristic (ROC) curve was used to calculate the optimal PNI and SII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
115
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(121 citation statements)
references
References 30 publications
2
115
0
4
Order By: Relevance
“…Recently, a new inflammatory index, the systemic immune-inflammation index (SII), defined as neutrophil × platelet/lymphocyte, integrates three inflammatory cells and has been shown to be promising [12]. The prognostic value of SII has been confirmed in various cancers, including NSCLC [13], small cell lung cancer [14], esophageal squamous cell carcinoma (SqCC) [15], breast cancer [16] and hepatocellular cancer [17]. However, to the best of our knowledge, the association of SII with tumor progression and the implication of SII in postoperative adjuvant chemotherapy in operable NSCLC patients remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new inflammatory index, the systemic immune-inflammation index (SII), defined as neutrophil × platelet/lymphocyte, integrates three inflammatory cells and has been shown to be promising [12]. The prognostic value of SII has been confirmed in various cancers, including NSCLC [13], small cell lung cancer [14], esophageal squamous cell carcinoma (SqCC) [15], breast cancer [16] and hepatocellular cancer [17]. However, to the best of our knowledge, the association of SII with tumor progression and the implication of SII in postoperative adjuvant chemotherapy in operable NSCLC patients remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The prognostic nutritional index (PNI), which is calculated from the serum albumin concentration and total lymphocyte count in the peripheral blood, is an index that reflects chronic inflammation, immune system and nutritional status and indicates prognostic significance in different patients ( 8 ). PNI had been described as a simple and objective indicator of adverse outcomes not only in chronic conditions, such as hepatocellular carcinoma ( 9 ), chronic heart failure ( 10 ) and different cancer types ( 11 ), but also in acute illnesses, including acute coronary syndrome ( 12 ), acute heart failure ( 13 ) and stroke ( 14 ). Furthermore, a previous study demonstrated an association between PNI and AKI in patients with normal serum creatinine levels who underwent coronary artery bypass grafting ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Systemic immuneinflammation indices 9 (neutrophil-to-lymphocyte ratio (NLR), 10 platelet-to-lymphocyte ratio (PLR) 11 ), gammaglutamyltransferase to albumin ratio index (GARI) 12 and gamma-glutamyltransferase to platelet ratio index (GPRI) 13 have been proven in many studies to effectively identify high-risk HCC patients with a poor prognosis, and CA125 and prognostic nutritional index (PNI) were associated with tumor recurrence after liver resection. 14,15 These models are constructed through blood biochemical indicators that are relatively easy to obtain in the clinic and are related to the physiological functions of the liver. Importantly, the prognosis of HCC patients depends not only on tumor burden (tumor number, size, portal vein thrombosis and extrahepatic spread) but also on underlying liver function.…”
Section: Introductionmentioning
confidence: 99%